DIAGNOSIS OF FAULT USING STATE OBSERVERS IN SYSTEMS WITH DYNAMIC VIBRATIONS ABSORBERS (DVAs) - Melo, Gilberto Pechoto; Fernandes, Fernando Vitoriano; Koroishi, Edson Hideki; Fernandes, Vinícius (Revista Tecnológica, 2011)
Abstract. Lately, the Dynamic Vibrations Absorbers (DVAs) have been widely applied in machines, mechanical equipments, and civil construction, aiming to assure satisfactory operation conditions, safety and confort. In this context there is a lot of effort in order to design control systems abble to attend new developed structures. The main goal of this work is to use DVAs with vibrating blades, and discribe the technique of State Observers to detect fault in systems with varying in frequency ( to be apply in the next work). The purpose is to syncronize a DVA for a specific primary structure and apply the global and robust State Observers to detect and locate fault in especified parameters of the system. With the preliminary results it was possible to design a DVA using the finite element method( plate elements) at the vibrating blade. The primary structure was excited with 60 and 450 rad/s harmonic forces.